Issues in the Design of Fiscal Policy Rules. (September 2015) - Portes, Jonathan; Wren‐Lewis, Simon
Abstract : Theory suggests that government should smooth taxes and spending, and adjustments in the level of debt should be gradual. Fiscal rules should therefore relate to deficits rather than debt. Rules should also reflect constraints on monetary policy. In normal times, rules should reflect political and institutional considerations, such as the potential for 'deficit bias', and the effectiveness of any fiscal council. For example, governments without a history of bias might target deficits five years ahead. However, if interest rates hit the zero lower bound, fiscal and monetary policy coordination is required, and here fiscal councils can also have an important role.